NUTRITIONAL STATUS ACCORDING TO Z-SCORE (WHO 2006) IN CHILDREN ≤ 5 YEARS OLD AT THE PEDIATRIC DEPARTMENT OF 108 MILITARY CENTRAL HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objective: To assess the nutritional status of children ≤ 5 years old at 108 Military Central Hospital.Subjects and methods: A cross-sectional descriptive study was conducted on 433 children ≤ 5 years old treated at the Pediatric Department of 108 Military Central Hospital from February 2023 to February 2025. The nutritional status of children was assessed using the Z-Score according to the World Health Organization (WHO 2006) growth standards.Results: Of the 433 children participating in the study, 60.3% were boys and 39.7% were girls (boys/girls ratio 1.5:1). The overall malnutrition rate was 42.4%, with stunting accounting for the highest proportion (28%), followed by underweight (9.5%) and wasting (4.9%). The rate of overweight/obese children was 11.3%. Children with respiratory illnesses had the highest rate of malnutrition compared to other disease groups. The majority of hospitalized children had acute illnesses (59.6%), while 40.4% had chronic illnesses.Conclusion: The rate of malnutrition in children ≤ 5 years old treated at the hospital remains high, with stunting being the predominant form of malnutrition
Keywords: malnutrition, Z-Score WHO 2006, children under 5 years old, stunting.